If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.17x + 0.7(x + -2) = 0.01(4x + -1) Reorder the terms: 0.17x + 0.7(-2 + x) = 0.01(4x + -1) 0.17x + (-2 * 0.7 + x * 0.7) = 0.01(4x + -1) 0.17x + (-1.4 + 0.7x) = 0.01(4x + -1) Reorder the terms: -1.4 + 0.17x + 0.7x = 0.01(4x + -1) Combine like terms: 0.17x + 0.7x = 0.87x -1.4 + 0.87x = 0.01(4x + -1) Reorder the terms: -1.4 + 0.87x = 0.01(-1 + 4x) -1.4 + 0.87x = (-1 * 0.01 + 4x * 0.01) -1.4 + 0.87x = (-0.01 + 0.04x) Solving -1.4 + 0.87x = -0.01 + 0.04x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.04x' to each side of the equation. -1.4 + 0.87x + -0.04x = -0.01 + 0.04x + -0.04x Combine like terms: 0.87x + -0.04x = 0.83x -1.4 + 0.83x = -0.01 + 0.04x + -0.04x Combine like terms: 0.04x + -0.04x = 0.00 -1.4 + 0.83x = -0.01 + 0.00 -1.4 + 0.83x = -0.01 Add '1.4' to each side of the equation. -1.4 + 1.4 + 0.83x = -0.01 + 1.4 Combine like terms: -1.4 + 1.4 = 0.0 0.0 + 0.83x = -0.01 + 1.4 0.83x = -0.01 + 1.4 Combine like terms: -0.01 + 1.4 = 1.39 0.83x = 1.39 Divide each side by '0.83'. x = 1.674698795 Simplifying x = 1.674698795
| x+5/2=15-x/3 | | 4p+3=5+3p | | X(3X-14)=-9 | | -2(4y-3)-y=-2[y-3) | | 6.2x-3=5.2 | | x+1.6x=88 | | 12+9*n=6 | | 6b+8=3b-12 | | 3.8+4=2.8x | | 12+9xn=6 | | 3.8+4=28x | | x+1.6x=87 | | 3-12= | | s=qs+q | | 6(h+3)-7h-4= | | b=qs+q | | x+1.6x=96 | | 2(3x-4)=4x+12 | | x^2+jx+6=0 | | 1/3(6y-9)=-2y+13 | | x-1=6x-18 | | 5x-7/3-4=3/5-2+5x/6 | | 2x-x+9+3x-3=16 | | 3(y+1)-y=2y+3 | | 5x-11x-12=0 | | 3.2+0.4= | | 50x-70-120=18-10+25x | | y=2x-6x-1 | | 50x-70-120=18-10+70+120 | | 4(d+-3)=2d | | 4(d-3)=12z | | 8x+12=5x-21 |